Hektor’s framework, embodiment and superabundance in research on information activities in serious leisure - Weber, Jan Raoul (Information Research an international electronic journal, 2025)
Introduction. In 2016, Hartel et al. introduced Hektor’s framework of information activities as a tool for analysing human information behaviour in serious leisure. They also noted a lack of attention towards embodiment and superabundance. This study aims to examine serious leisure papers published between 2017 and June 2023 to determine if and how Hektor’s framework has been utilised and if embodiment and superabundance have been addressed. Method. A systematic review of serious leisure literature from 2017 to June 2023 in selected journals and databases is conducted. Analysis. The final sample of nineteen publications is thematically categorised and analysed to identify common patterns and themes. Results. Hektor’s framework is mentioned in nine publications, but only used as a structuring tool in five. Embodiment is discussed in thirteen publications, with body as information source and body as sign emerging as categories for analysis. Two studies briefly touch upon superabundance, but do not investigate it further. Conclusions. Hektor’s framework is only one of several being used, but using it leads to more comparable results. Embodiment appears to be of high interest, with the body as information source and body as sign being useful categories for analysis. Superabundance still lacks attention.